2019
DOI: 10.1190/int-2018-0225.1
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution neural networks for tracking seismic horizons from few training images

Abstract: Detecting a specific horizon in seismic images is a valuable tool for geological interpretation. Because hand-picking the locations of the horizon is a time-consuming process, automated computational methods were developed starting three decades ago. Older techniques for such picking include interpolation of control points however, in recent years neural networks have been used for this task. Until now, most networks trained on small patches from larger images. This limits the networks ability to learn from la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Another work related to ours is [36]. Authors try to mitigate the high cost of manual annotations of seismic images by introducing an approach which can utilize sparse annotations instead of the commonly used dense segmentation masks.…”
Section: Related Workmentioning
confidence: 99%
“…Another work related to ours is [36]. Authors try to mitigate the high cost of manual annotations of seismic images by introducing an approach which can utilize sparse annotations instead of the commonly used dense segmentation masks.…”
Section: Related Workmentioning
confidence: 99%
“…It was shown previously [Peters et al, 2018] that it is possible to track a single horizon using the Unet based networks and loss-functions that compute losses and gradients based on the sparse labels only. Therefore, there was no need to work in small patches around labeled points or manually generate fully annotated label images.…”
Section: Horizon Tracking By Interpolation Of Scattered Picksmentioning
confidence: 99%
“…are the labeled features that need to be recovered. Using deep convolution networks is therefore a straight forward extension of existing neural network technology and have been studied recently by many authors (see for example [Peters et al, 2018, 2019, Wu and Zhang, 2018, Waldeland et al, 2018, Poulton, 2002, Leggett et al, 2003, Lowell and Paton, 2018, Zhao, 2018 and references within). However, while it seems straight forward to use such algorithms, there are some fundamental differences between vision-related applications to seismic processing.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, new neural network designs have shown that they can provide high-quality interpretations. In particular, U-nets were used for the interpretation of geological units [Peters et al, 2019a,b], horizons [Peters et al, 2018], salt [Zeng et al, 2018], and faults [Wu et al, 2019, Zhang et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Peters et al [2018Peters et al [ , 2019a introduced partial loss-functions for non-linear regression and classification for seismic interpretation. These type of loss functions measure misfit at the known and sparsely distributed annotated label pixels only.…”
Section: Introductionmentioning
confidence: 99%